Mitochondrial metabolism and respiration adjustments following temperature acclimation in Daphnia magna - Hoffschröer, Nadine (2024)
Seasonal temperature changes and local variations in the water column challenge lentic zooplankton in their habitat. At the cellular level, exposure to varying temperatures affects the mitochondrial functional properties of poikilothermic organisms. Metabolic enzymes that supply reduced substrates to the electron transport chain and elements of the oxidative phosphorylation system must therefore adjust their activity and flux rates to the altered temperature conditions. In the present study, Daphnia magna respiration was analyzed in response to acute and chronic changes in ambient temperature. Oxygen consumption as well as substrate and electron flux rates were measured at the animals´ acclimation temperature and at two additional acute temperatures. High activity of citrate synthase (CS) in cold-acclimated animals (10 °C) may have resulted from mitochondrial quantitative adjustments. However, thermal sensitivity of the functional properties of mitochondrial enzymes was greater in warm-acclimated animals (30 °C). In whole animals, temperature-induced changes were partly compensated by acclimation, but these changes were promoted by acclimation in the case of the mitochondrial electron transport chain. Thus, respiration realised in whole animals was limited by the provision of reduced substrates in the tricarboxylic acid cycle rather than by restrictions of the respiratory chain complexes. This may minimize production of reactive oxygen species and resulting damage and reduce waste of substrates from the animals’ energy reserves. Still, the integrated biomarker response indicated increased defense against oxidative stress at elevated temperatures.